EMPOWERING THE ELDERLY THROUGH SELF-RELIANT COMMUNITY NETWORKS AND COLLABORATIVE LEARNING: AN APPROACH TO REDUCING URBAN SOCIAL INEQUALITIES. - Phukamchanoad, Phusit (Scientific Culture, 2025)
Purpose: This participatory action research enhances the potential of active elderly individuals in urban communities, focusing on four communities near Wat Pracharabuedham in Dusit District, Bangkok. It examines inequality affecting the elderly, identifies community assets, and develops mechanisms to improve their mental and social well-being. Methods: The Using an integrated approach of "understanding, accessibility, and development," qualitative data from 40 participants--including elderly residents, public health volunteers, community leaders, local government representatives, youth, and the Bhat Phat Community Occupation Group--revealed widening generational gaps and economic pressures forcing families to rely on multiple income sources, typically requiring at least two earners per household. Results: The results are categorized into three key outcomes, these pressures marginalized unemployed elderly individuals, who were often viewed as burdens, reducing their mental and social quality of life. To address these challenges, the study empowered elderly individuals to act as key drivers of community development. By leveraging community assets, they were enabled to generate "creative energy" through innovative income-generating activities, which supplemented their families' income. Conclusion: This approach fostered self-reliance, personal growth, and recognition of the elderly as sources of wisdom, leading to greater respect from younger generations. The "fried egg model" was adopted, preserving core values (the yolk) while adapting to changing social and economic conditions through flexible strategies (the egg white). Soft skills development and collaborative learning among community members and networks established a sustainable framework for elderly empowerment and reduced socio-economic inequalities.